2011
DOI: 10.1021/ol102757v
|View full text |Cite
|
Sign up to set email alerts
|

C−O Hydrogenolysis Catalyzed by Pd-PMHS Nanoparticles in the Company of Chloroarenes

Abstract: Catalytic Pd(OAc) 2 and polymethylhydrosiloxane (PMHS), in conjunction with aqueous KF, and a catalytic amount of an aromatic chloride, effects the chemo, regio, and stereoselective deoxygenation of benzylic oxygenated substrates at room temperature in THF. Preliminary mechanistic experiments suggest the process to involve palladium-nanoparticle catalyzed hydrosilylation followed by C-O reduction. The chloroarene additive appears to facilitate the hydrogenolysis process through the slow controlled release of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
61
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 26 publications
4
61
0
Order By: Relevance
“…The corresponding benzylic alcohols and secondary alcohol analogues could also be converted into their respective methylene hydrocarbons by the PdCl 2 /PMHS system. In this context, Maleczka et al [10] has reported very recently an important and effective catalytic system with PdA C H T U N G T R E N N U N G (OAc) 2 (5 mol%) and PMHS (2.5 equiv.) It is a by-product of the organosilicon industry and an inexpensive hydrosilane that can be employed as the stoichiometric reducing agent in organic synthesis.…”
mentioning
confidence: 99%
“…The corresponding benzylic alcohols and secondary alcohol analogues could also be converted into their respective methylene hydrocarbons by the PdCl 2 /PMHS system. In this context, Maleczka et al [10] has reported very recently an important and effective catalytic system with PdA C H T U N G T R E N N U N G (OAc) 2 (5 mol%) and PMHS (2.5 equiv.) It is a by-product of the organosilicon industry and an inexpensive hydrosilane that can be employed as the stoichiometric reducing agent in organic synthesis.…”
mentioning
confidence: 99%
“…84 Mild deoxygenation of aryl ketones to the corresponding methylene compounds has been achieved using PMHS, fluoride ion, and catalytic Pd in the presence of aryl chlorides. 85 The aryl chloride is thought to facilitate the hydrogenolysis process through slow release of HCl. The same conditions could be used for Odebenzylation of other species, including benzyl ethers, benzyl esters (as lactones), tertiary benzyl alcohols, or tertiary benzyl epoxides.…”
Section: %mentioning
confidence: 99%
“…In the latter two cases, chiral integrity at the benzylic position was retained. 85 The carbonyl group of amides can also be reduced using PMHS to provide the corresponding amine species. In the presence of an iron carbonyl catalyst, a variety of aromatic, aliphatic, heteroaromatic, and heterocyclic amides were smoothly reduced to the corresponding amines (eq 41).…”
Section: %mentioning
confidence: 99%
“…12 Many catalytic systems are being optimized to selectively cleave CAO bonds in a molecule demonstrating not only the efficacy of catalytic systems but also highlighting the importance of the CAO bond breaking strategy. 13 To realize the synthesis of the natural compound, kigelin, (2) we targeted synthesis of key chiral intermediate 13 and for the synthesis of key compound 13 we needed to synthesise isoelemicine 11 which was synthesized as reported in the literature. 14 Synthetic procedure commenced with the allyation of phenol 8a to get compound 9 which on Claisen rearrangement gave the phenolic compound 10.…”
Section: Introductionmentioning
confidence: 99%